EMBR-22. RATIONAL DEVELOPMENT OF SYNERGISTIC THERAPIES ALONGSIDE BMI1 INHIBITION FOR GROUP 3 MEDULLOBLASTOMA. (1st June 2021) - Bakhshinyan, David; Adile, Ashley A; Venugopal, Chitra; Brown, Kevin; Chan, Katherine; Qazi, Maleeha A; Chokshi, Chirayu; Gwynne, William D; Tieu, David; Moffat, Jason; Singh, Sheila
Abstract: Medulloblastoma (MB) is the most common pediatric brain tumor. Of its four distinct molecular subgroups, Group 3 MBs are associated with increased risk of recurrence, metastasis and overall poor patient outcome. In recent years, small molecule inhibitors targeting BMI1 have shown to be efficacious against several types of malignant tumors including pediatric MB. Although in vivo studies provide a promising proof-of-concept for the therapeutic targeting of BMI1 in Group 3 MB, mice that receive treatment eventually succumb to their disease. These results suggest that additional mechanisms may underlie the maintenance of MB and underscores the main obstacle in treating a constantly evolving tumor. After initial preclinical validation of BMI1 inhibitor PTC-596, DNA barcoding clonal tracking technology was leveraged to profile in vivo clonal dynamics of Group 3 MB in response to the established chemoradiotherapy regimen alone and in combination with PTC-596. Comparison of clonal composition of the tumors extracted from the brains and spines post-treatment revealed the persistence of a small number of clones with the ability to escape therapy and drive subsequent tumor expansion. In order to better understand molecular susceptibilities of MB cells post BMI1 inhibition, we undertook an in vitro genome-wide CRISPR/Cas9 screening to identify context-specific MB regulatory pathways to be synergistically targeted along with BMI1. By comparing the results of the in vitro genome wide CRISPR/Cas9 screen to the essential genes in human neural stem cells (hNSCs), we identified several context specific regulators of mTOR, AKT and PLK1 pathways. The combined treatment alongside PTC-596 has demonstrated synergistic efficacy against MB cells with minimal toxicity to hNSCs in vitro and is currently being evaluated in preclinical studies. This study provides the foundation for clinical validation of small-molecule inhibitors synergistic with PTC-596 to improve the durability of remissions and extend survival of patients with treatment-refractory Group 3 MB.